Pengaruh Beban Kerja Dan Motivasi Kerja Terhadap Kinerja Petugas Pemadam Kebakaran Dinas Penanggulangan Kebakaran Dan Penyelamatan Sektor Johar Baru - Desak Gede Roche Dian Novita; Dicky Almiftah (Jurnal Ilmu Administrasi Publik, 2023)
This research aims to analyze and measure the effect of workload and work motivation on the performance of firefighters in the Fire and Rescue Service of the Johar Baru sector. The sample consisted of 44 fire department employees selected through saturated sample technique which took the entire population as a sample. Data were collected through questionnaires and analyzed using multiple regression analysis techniques using the SPSS for Windows ver. 26. The results showed that: (1) workload has a positive and significant influence of 40.5% with a  significance value of 0.000, (2)  work motivation has a positive and significant influence of 21.6% with a significance value of 0.004, and (3) simultaneously, workload and work motivation have a positive and significant influence on performance of 48.4% with a significance value of 0.000.